2022
DOI: 10.34133/ultrafastscience.0002
|View full text |Cite
|
Sign up to set email alerts
|

Transient Superdiffusion of Energetic Carriers in Transition Metal Dichalcogenides Visualized by Ultrafast Pump-Probe Microscopy

Abstract: Because of the strong Coulomb interaction and quantum confinement effect, 2-dimensional transition metal dichalcogenides possess a stable excitonic population. To realize excitonic device applications, such as excitonic circuits, switches, and transistors, it is of paramount importance for understanding the optical properties of transition metal dichalcogenides. Furthermore, the strong quantum confinement in 2-dimensional space introduces exotic properties, such as enhanced phonon bottlenecking effect, many-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In transport regime iii, the population appears to contract on itself over 500 ps, indicating negative effective diffusion. This intriguing effect has been observed and predicted in a variety of systems including 2D materials and molecular crystals and is explained by competing spatio-kinetic effects when multiple photoexcited species are present. Transient reflectance spectra of CsRe 6 Se 8 I 3 (Figure f), which displays a dominant response due to photoinduced bleaching of the lowest optical transition, support the notion that several species or competing processes are present: three components with subtly different spectral contributions and lifetimes of ∼0.3, 11, and 440 ps are required to model the spectral evolution via global analysis (Figure S5).…”
mentioning
confidence: 71%
“…In transport regime iii, the population appears to contract on itself over 500 ps, indicating negative effective diffusion. This intriguing effect has been observed and predicted in a variety of systems including 2D materials and molecular crystals and is explained by competing spatio-kinetic effects when multiple photoexcited species are present. Transient reflectance spectra of CsRe 6 Se 8 I 3 (Figure f), which displays a dominant response due to photoinduced bleaching of the lowest optical transition, support the notion that several species or competing processes are present: three components with subtly different spectral contributions and lifetimes of ∼0.3, 11, and 440 ps are required to model the spectral evolution via global analysis (Figure S5).…”
mentioning
confidence: 71%
“…In addition, the room-temperature carrier mobility of TMDCs is up to 1000 cm 2 V −1 s −1 [12]. Zhou et al directly observed the ultrafast transport of non-equilibrium excitons in monolayer WSe 2 , MoWSe 2 and MoSe 2 , which is conducive to the realization of ultra-fast optoelectronic devices [78].…”
Section: Two-element 2d Materialmentioning
confidence: 99%
“…26 On the other hand, the slow negative diffusion observed in monolayer Mo 1−x W x Se 2 and MoSe 2 is explained by the spatial variation of a defect-filling effect. 29 Nevertheless, direct experimental evidence supporting these interpretations is currently lacking. In this study, the carrier transport in monolayer MoS 2 (1L-MoS 2 , Sample preparation is shown in Supporting Information Section 1) was investigated through the spatiotemporal mapping of carrier density using TAM.…”
mentioning
confidence: 99%
“…Our TAM results demonstrate the cascaded carrier transport dynamics that are consistent with the previous findings in multilayer WS 2 and monolayer WSe 2 . 26,29 The diffusion dynamics of hot carriers and band edge C-excitons were separately measured, providing novel insight into the negative diffusion process.…”
mentioning
confidence: 99%
See 1 more Smart Citation